Optimization of PFN thickness in inverted high-performance PTB7:PC70BM solar cells. (March 2019) - Reséndiz, L.; Balderrama, V.S.; Lastra, G.; Ramírez, M.; Cabrera, V.; Estrada, M.
Highlights: Organic solar cell with 10 nm of PFN showed an efficiency of 7.41%. Experimental and simulated J-V curves for PTB7:PC70 BM and PCDTBT:PC70 BM are in good agreement. The experimental J-V curves were simulated by varying the work function of the ITO material. Abstract: Organic solar cells (OSCs) made from PTB7:PC70 BM, with different thicknesses of a conjugated electrolyte PFN (0, 5, 7, 10, and 15 nm) used as the cathode buffer layers, were fabricated partially in air. OSCs with 10 nm of PFN were the most efficient in experimental tests, at 7.41%. Numerical simulations of the cells were also performed using the physics-based Silvaco/ATLAS CAD simulator, which describe the OSCs using the metal-insulator-metal (MIM) model. Simulations were used to determine the optimum values of PFN thickness for achieving high overall performance, which lies in the region from 5 to 10 nm.